Humour and Laughter in History Transcultural Perspectives - Cheauré, Elisabeth; Nohejl, Regine (transcript Verlag, 2014)
Humour can be used as a »weapon« or as a means of coping with problematic historical events, especially in times of war and crisis. The book presents examples from different cultures (Russia, Europe, USA), from different historical epochs (from the Napoleonic era up to the current time) and from different medias (caricature, journalism, film). By looking at the individual cases it becomes possible to recognize some general structural patterns and to gain a deeper insight into the »functioning« of humour and laughter.